Self‐assessment of eating disorder recovery: Absence of eating disorder psychopathology is not essential - Slof‐Op 't Landt, Margarita C.T.; Dingemans, Alexandra E.; de la Torre Y Rivas, Jésus; van Furth, Eric F. (The International journal of eating disorders, 2019)
Objective The definition of recovery in eating disorders (EDs) according to researchers is not necessarily similar to the patient definition. This study aimed to explore the concept of recovery as assessed by those affected by an ED themselves. Method Participants from the Netherlands Eating disorder Registry (NER) who reported an (former) ED diagnosis (n = 814) assessed their own recovery level: current ED, partial or full recovery. Furthermore, research‐based criteria (Bardone‐Cone et al., Behaviour Research and Therapy, 2010, 48, 194–202) were applied to define recovery. Within the self‐assessed full recovery group (n = 179), participants who also fulfilled the research‐based criteria were compared to those who were only recovered based on self‐assessment in the following domains: ED psychopathology, psychiatric comorbidity, quality of life, and social and societal participation. Results Ninety‐six of the participants (54%) who considered themselves recovered did not fulfill the research‐based definition. The two recovery groups did not significantly differ in psychiatric comorbidity, quality of life, and social and societal participation. Discussion Absence of ED characteristics was not essential for individuals to consider themselves recovered. Although the self‐assessed recovery status may be subjective, it does advocate the use of additional health indicators besides ED psychopathology when defining recovery.